1986
DOI: 10.1136/bmj.293.6552.917
|View full text |Cite
|
Sign up to set email alerts
|

Determinants and importance of stress hyperglycaemia in non-diabetic patients with myocardial infarction.

Abstract: Determinants and importance of stress hyperglycaemia in non-diabetic patients with myocardial infarctionDeterminants of plasma glucose concentrations were studied in patients on admission to hospital with confirmed acute myocardial infarction but without previous glucose intolerance as evidenced by raised concentrations of glycosylated haemoglobin (HbA&,). Mortality in hospital increased significantly with increasing plasma concentrations ofglucose in patients with both normal (p<0O0001, n=311) and borderline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
142
2
6

Year Published

1998
1998
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 245 publications
(156 citation statements)
references
References 25 publications
6
142
2
6
Order By: Relevance
“…However, the relation between glucose concentrations and infarct size is controversial. O'Sullivan et al (15) and Thomassen et al (16) found no correlation between glucose levels and infarct size as reflected in peak levels of cardiac enzymes, whereas Oswald et al (17) and Bellodi et al (18) found a weak relation between plasma glucose concentrations and infarct size. Recently, Ishihara et al (15) found lower LVEF among patients with AMI and admission glucose Ͼ10 mmol/l (14).…”
Section: Fasting Glucose and Left Ventricular Functionmentioning
confidence: 96%
See 1 more Smart Citation
“…However, the relation between glucose concentrations and infarct size is controversial. O'Sullivan et al (15) and Thomassen et al (16) found no correlation between glucose levels and infarct size as reflected in peak levels of cardiac enzymes, whereas Oswald et al (17) and Bellodi et al (18) found a weak relation between plasma glucose concentrations and infarct size. Recently, Ishihara et al (15) found lower LVEF among patients with AMI and admission glucose Ͼ10 mmol/l (14).…”
Section: Fasting Glucose and Left Ventricular Functionmentioning
confidence: 96%
“…Elevation of fasting glucose levels in AMI may incorporate the cumulative effects of activation of multiple neurohormonal pathways such as catecholamines, cortisol, and growth hormone (17,26), which can produce or augment insulin resistance (27)(28)(29). Activation of the renin-angiotensin system (30) and the effect of increased circulating cytokines (31) such as tumor necrosis factor-␣ in the setting of AMI infarction may also contribute to a reduction in peripheral insulin sensitivity (32,33).…”
Section: Mechanism Of Stress Hyperglycemiamentioning
confidence: 99%
“…In the setting of acute myocardial infarction [1], hyperglycemia is not simply a marker of pre-existing diabetes or glucose intolerance but it may represent a stress response to myocardial injury mainly related to acute catecholamine release [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…yperglycemia at the time of hospital admission has been associated with shorter survival after acute myocardial infarction in patients both with and without diabetes (1)(2)(3)(4)(5). It is not fully understood whether this is due to the acute development of stress hyperglycemia or to the quality of long-term metabolic control before the event (6).…”
mentioning
confidence: 99%